Scale Measurement Development for Sustainable Fashion Design Curriculum Through Technopreneur Orientation - Rahayu Purnama; Melly Prabawati; Vivi Radiona; Rosita Mohd Tajuddin; Shaliza Mohd Shariff; Muhamad Aiman Afiq Mohd Noor (International Journal of Engineering, Science and Information Technology, 2026)
This article describes the development and validation of the sustainable fashion design curriculum through technopreneur orientation. This quantitative 98-item scale measures Indonesian university fashion design students'(80) toward sustainable fashion design curriculum. The validity and reliability of the scale was statistically tested by calculating the Corrected Item-Total Correlation, Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO MSA) via an Exploratory Factor Analysis, descriptive statistics, Cronbach's Alpha, and a con?rmatory factor analysis. The results of the principal component factor analysis indicate that the scale consists of the following four dimensions: entrepreneurial orientation, technopreneur orientation, fashion sustainability and sustainable fashion design curriculum. The reliability test evaluated the ninety-eight (98) items in the study that were divided into five (4) constructs Entrepreneur Orientation (EO), Technopreneur Orientation (TO), Fashion Sustainability (FS), and Sustainable Fashion Design Curriculum (SFDC). The measurement of the scale are con?rmed by the CFA. Internal reliability was found using the total item correlation value corrected for all items 0.3, Cronbach's Alpha values are more significant than 0.6 and KMO MSA value above 0.5. Cronbach's Alpha coefficients for all constructs showed excellent reliability, with Technopreneur Orientation (TO) having the highest at 0.775 and the lowest at 0.832. Technopreneur Orientation (TO) had the most significant score of 0.832, while Sustainable Fashion Design Curriculum (SFDC) had the lowest score of 0.775. The findings revealed that all 98 items in the four (4) constructs had a considerable internal disagreement. As a result of the pilot investigation, the items in this study's questionnaires were well-founded in previous literature and highly trustworthy and appropriate for study inferences. The results confirm the reliability and validity of the faces of the adapted instrument in the pilot study.